2022
DOI: 10.1159/000526227
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Tongue Pressure and Salivary Bacteria in the Older Adults Requiring Long-Term Care

Abstract: <b><i>Introduction:</i></b> Aspiration pneumonia, an important issue for the older adults, is caused by an increase in pathogenic microorganisms in the saliva, aspiration, and weakened host immunity. Recently, decreased tongue pressure has been reported to be associated with dysphagia. This study aimed to investigate the relationship between decreased tongue pressure and the number of bacteria in the saliva of the older adults requiring long-term care. <b><i>Methods:</i&g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
0
0
Order By: Relevance
“…It is important to reduce the number of bacteria in saliva, prevent aspiration, and improve the general condition of the patient to prevent aspiration pneumonia. Therefore, the importance of oral care for older adults and postoperative patients is widely reported [1][2][3][4][13][14][15][16][17]. Additionally, VAP in endotracheally intubated patients is directly related to survival outcomes and is a serious post-operative complication [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to reduce the number of bacteria in saliva, prevent aspiration, and improve the general condition of the patient to prevent aspiration pneumonia. Therefore, the importance of oral care for older adults and postoperative patients is widely reported [1][2][3][4][13][14][15][16][17]. Additionally, VAP in endotracheally intubated patients is directly related to survival outcomes and is a serious post-operative complication [6].…”
Section: Discussionmentioning
confidence: 99%
“…The human oral cavity contains many microorganisms (such as bacteria and fungi) that are controlled by oral cleansing methods such as oral intake, saliva secretion, and swallowing. However, bacterial counts are markedly increased in older adults with decreased oral functions, such as in cases of tongue pressure [ 1 ], fasting, or tube feeding [ 2 ], and in intubated patients [ 3 , 4 ]. The most effective method to reduce the oral bacterial count is rinsing the mouth, which is not possible in patients with decreased swallowing function or under intubation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“… 10 A significant association has been reported between decreased tongue pressure and increased salivary bacterial counts in institutionalized elderly patients requiring long-term care. 11 While these studies have indicated an association between poor oral function and increased salivary bacterial counts in the elderly, there have been no similar reports on perioperative patients. Identifying factors associated with increased salivary bacterial counts in perioperative patients would help determine which patients require focused oral care.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva was collected from the bottom of the mouth using a filter paper, according to the method described by Funahara. 11 The following variables were also collected from medical records: age, sex, primary disease, body mass index (BMI), serum albumin level, and operation time. Salivary bacterial counts were measured by real-time polymerase chain reaction (PCR; DNA extraction technique, primer, artificial DNA, and reaction conditions used were as previously reported by Tsuda.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation